The Routledge anthology of Renaissance drama - Barker, Simon.; Hinds, Hilary. (Routledge, 2003)
"Ten non-Shakespearean Renaissance plays and a masque have been brought together for the first time in what is a major text for students of English drama of the late sixteenth and early seventeenth centuries." "The Renaissance saw a dramatic explosion of such force that, four hundred years later, its plays are still amongst the most frequently performed and studied we have. This anthology offers a full introduction to Renaissance theatre in its historical and political context, along with newly edited and comprehensively annotated texts of the following plays: The Spanish Tragedy (Thomas Kyd); Arden of Faversham (Anon.); Edward II (Christopher Marlowe); A Woman Killed with Kindness (Thomas Heywood); The Tragedy of Mariam (Elizabeth Cary); The Masque of Blackness (Ben Jonson); The Knight of the Burning Pestle (Francis Beaumont); Epicoene, or the Silent Woman (Ben Jonson); The Roaring Girl (Thomas Middleton and Thomas Dekker); The Changeling (Thomas Middleton and William Rowley); and 'Tis Pity She's a Whore (John Ford)." "Each play is prefaced by an introductory headnote discussing the thematic focus of the play and its textual history, and is cross-referenced to other plays of the period that relate thematically and generically."--BOOK JACKET.